Initial assessment of bioavailable strontium at Oldupai Gorge, Tanzania: Potential for early mobility studies. (February 2020) - Tucker, Laura; Favreau, Julien; Itambu, Makarius; Larter, Fergus; Mollel, Neduvoto; Mwambwiga, Aloyce; Patalano, Robert; Roberts, Patrick; Soto, María; Mercader, Julio
Abstract: Strontium isotope analysis is a useful tool for tracing mobility and migration in past populations. For it to be employed, the 87 Sr/ 86 Sr values of the landscape must be well-understood. Bioavailable strontium is a combination of geological and atmospheric strontium available for use by plants and animals. In this study we begin mapping bioavailable strontium values around the Oldupai Gorge region so that this method may be utilized on archaeological hominins and animals in the future. We analyzed three plants from 33 localities across volcanic and metamorphic bedrock, including the regional drainage sump, Olbalbal. We found that bioavailable strontium in the region is homogeneous overall, with trends towards increasing values to the north and northeast and in Olbalbal. There was no difference between 87 Sr/ 86 Sr values of metamorphic and volcanic areas. Migrants from outside the study area with different isotopic values will be easily identifiable from the local residents. As a proof of concept, we analyzed 7 animal teeth (hippopotamus, crocodile, and equid) from Engaji Nanyori, a Bed III and IV site at Oldupai Gorge. We found that enamel and dentine which had been acetic acid treated to remove diagenetic strontium were significantly different from one another. All animals had higher 87 Sr/ 86 Sr values than the plant values, suggesting that modern and ancient bioavailable strontium values may have been different, likely due to environmental differences. Highlights: Bioavailable strontium in the Oldupai Gorge region is homogeneous. Metamorphic and volcanic areas have indistinguishable 87 Sr/ 86 Sr values. Modern and ancient bioavailable strontium appear to be different. Animals which are migratory now may have been resident in the past.